A partial least squares path model of repurchase intention of supermarket customers - Noyan, Fatma; Simsek, Gulhayat Golbasi (ELSEVIER SCIENCE BV, 2012)
The objective of this paper is to model which aims to describe the extent to which customer intention to repurchase a service is influenced by customer perceptions of service quality, customer perceptions of product quality, comparative price perceptions, discount perceptions, trust, value, and customer satisfaction were considered as the major factors in the marketing literature. Partial Least Squares (PLS) Path Model approach was used to build a repurchase intention model in Turkish retailing sector with the theoretically hypothesized relationships among these major factors collecting the data from 1530 supermarket customers purchasing 102 different supermarkets. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Arasli
Keywords: Customer repurchase intention; satisfaction; partial least squares path model; PERCEPTIONS; Business & Economics